ANALYSIS OF HUMAN RESOURCES COMPETENCY DEVELOPMENT STRATEGY AMONG GEN Z IN FACING THE ERA OF SOCIETY 5.0 THROUGH THE SOAR METHOD CASE STUDY: PT. X - Ruth Meylina Manik; Yeni Absah; Anizar (CV. RADJA PUBLIKA, 2025)
The research used in the thesis entitled